American terrorist - Chin-Tanner, Tyler; Chin-Tanner, Wendy (A Wave Blue World, 2020)
"Embedded with an eco-terrorist group hellbent on explosive direct action, investigative journalist Owen Graham is enmeshed in a dangerous culture on the political fringe. Ordinary citizens, frustrated by inequality and oppression and a bureaucracy's resistance to change, are starting to go off the grid and disrupt the status quo. But the fringe is poised to go mainstream, and Owen's days as a passive observer are running short. While a series of escalating misunderstandings land an idealistic public school teacher in the middle of a hostage situation and the sights of an overeager federal agent who has been trailing Owen for months, he intervenes in a desperate split-second decision. Owen's old life is gone forever. Now he's on the run with a trio of fellow crusaders, all fighting for a better world but now labeled as terrorists by the government. Disparate people on all sides, each convinced they're right- and doing the right thing -- are now spinning towards each other in an inexorable spiral of violence."--Provided by publisher.